2020
DOI: 10.1002/epi4.12430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of epilepsy in Bangladesh: Results from a national household survey

Abstract: Objective To determine the prevalence and types of epilepsy in Bangladesh. Methods We conducted a nationwide population‐based cross‐sectional survey among Bangladeshi population of all ages, except children under one month. We surveyed 9839 participants (urban, 4918; rural, 4920) recruited at their households using multistage cluster sampling. Trained physicians with neurology background confirmed the diagnosis of suspected epilepsy cases identified by interviewer‐administered questionnaires. We reported the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…12 Studies including children and adult populations showed higher prevalence than pediatric studies. [13][14][15] Since 1998, no other studies on epilepsy prevalence in Morocco have been done. In the Standards for epidemiologic studies and Surveillance of Epilepsy performed by the ILAE epidemiology commission, surveys conducted by telephone were encouraged but the validity and clinical detail from self-reports and proxy reports must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies including children and adult populations showed higher prevalence than pediatric studies. [13][14][15] Since 1998, no other studies on epilepsy prevalence in Morocco have been done. In the Standards for epidemiologic studies and Surveillance of Epilepsy performed by the ILAE epidemiology commission, surveys conducted by telephone were encouraged but the validity and clinical detail from self-reports and proxy reports must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Epileptic seizure is a chronic brain disorder caused by abrupt anomaly of brain nerve cells. It gives rise to abnormal electrical activity in human brain due to the improper firing of brain neurons [1][2][3][4][5]. Seizures have intricate and distinct traumatic symptoms including imbalance body movement, jerking of body parts, loss of consciousness, stroke and disruption of cognitive functions [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Seizures have intricate and distinct traumatic symptoms including imbalance body movement, jerking of body parts, loss of consciousness, stroke and disruption of cognitive functions [2,4]. Severe occurrence of epileptic seizure may even cause death if the patient during seizure attack is unattended [3,5]. Around the globe, approximately 50 million people suffer from epileptic seizure; among them nearly 80% patients live in developing countries [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Epilepsy affects 0.5%-1% of the children, incidence varies from high income to low middle income countries . 3 In Bangladesh, it is estimated to be 8.2/1000 (95% CI 3.4-13.0) in children aged <18 years 4 whereas Pakistan showed up to 9.99 / 1000 population. 5 The electroencephalogram (EEG) is the procedure for detecting brain waves which showed electrical activity of the brain using leads made up of metallic electrodes which records different types of lines/waves on paper.…”
Section: Introductionmentioning
confidence: 99%